Metode Multiv Soil Layering Dalam Penyisihan Parameter TSS Limbah Cair Kelapa Sawit Dengan Variasi Hydraulic Loading Rate (HLR) Dan Material Organik Pada Lapisan Anaerob - Rahmadani Mutia; Shinta Elystia; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
This study uses Multi Soil Layering (MSL) to cultivate oil palm liquid waste. The purpose of the research was to determine the efficiency of contaminant parameter Total Suspended Solid (TSS) allowance, study of the influence factors of variation of organic material in the mix on a layer of soil anaerobic and variation of Hydraulic Loading Rate (HLR) of the efficiency of the liquid waste processing with MSL, and compare research results with Keputusan Menteri Lingkungan Hidup No. 51 in 1995. In this study used two reactors measuring 30 cm x 26 cm x 35 cm, consisting of aerobic and anaerobic layer. Aerobic layer on both the same reactor, namely the gravel and perlit measuring 3-5 mm, while the second reactor anaerobic layer is distinguished, where the soil is a mixture of 1 reactors with active charcoal coconut shell and on reactor 2 is a mixture of ground with active charcoal banana peels by a ratio of 2: 1. Liquid waste oil palm streamed with the variation of Hydraulic Loading Rate (HLR) of 500 L/m2 day, 750 L/m2 day, 1000 L/m2 day at each reactor. TSS concentration before processing by the method of MSL is 890 mg/L, and, after processing concentration TSS is down to 100-240 mg/L. Variation of organic material gives the effect on the efficiency of the allowance which the TSS on charcoal activated coconut shell that has larger pores can do more MSL maximum mechanism. Variation of Hydraulic Loading Rate (HLR) also exert influence, where the smaller the HLR is given then the efficiency will be high. Efficiency of TSS removal are 79,77-88,76% in reactor 1 and 73,03-79,77% in reactor 2.Keywords: Efficiency, Hydraulic Loading Rate (HLR), Multi Soil Layering (MSL), Palm Liquid Waste, Organic Material.